IMPLIKASI SISTEM PENGENDALIAN INTERNAL KEUANGAN PADA ORGANISASI KLUB SEPAKBOLA: STUDI KASUS DI PT. AREMA INDONESIA - Ina Prameswari (Ma Chung Press, 2015)
The purpose of this research provide exploration the influences of internal control system in aacordance to achived good financial performance in the PT. Arema Indonesia. Internal control system is not only applied in the business organization, however it’s also needed in the football organization which it recently has been developing into a business industry. Currently, PT. Arema Indonesia facing difficulties to manage and develop their financial sources. Using qualitative case study method as the research design be able to find out how the internal control system can solve problems of financial management of PT. Arema Indonesia which it’s considering they have been through financial crises. Mostly come out from the excess of expenses rather than income because of high cost of operating and fixed cost for salary of the football players and coaches. The result of this research showed that basically PT. Arema Indonesia has have incapabilities to applied the internal control system in their financial management. It is proven by some obstacles during the implementation activities of control system. One of them is weak control on expenses of PT. Arema Indonesia when facing financial deficit caused by excessive compared with smaller income. This research is expected to provide contribution on the development of internal control system in football organization considering to achieve sustainability and increasing the organization value in PT. Arema Indonesia.